A bipolar charge transport model to simulate the impact of nanometric scale processes on the space charge behaviour in polyethylene. (27th September 2022) - Le Roy, S; Hoang, M Q
Abstract: Predicting the electric field distribution in polymers used as electrical insulating materials remains the Holy Grail, as the presence of charges disturbs the Laplacian electric field. Charges arising from the electrodes are one of the dominant mechanisms of charge generation, particularly in polyethylene-based materials. Hence, the nanometric scale processes at play at the interface exert a non-negligible impact on charge injection. In this study, a bipolar charge transport model developed in 2D is used to simulate the effects of several nanometric scale processes, such as the variation of the barrier height linked to the chemical structure of the material at the interface and surface roughness. Simulation results with regard to the net charge density. current and the recombination rate will be compared to the case where no specific supplementary hypothesis is set at the electrodes. Finally, simulations are performed for a combination of roughness and barrier height variations along the electrodes.